Peningkatan Keterampilan Menulis Hasil Wawancara Peserta Didik Melalui Metode Outdoor Study - Mirva Faudati; Siti Rochmiyati (UNIB Press, 2023)
The objective of this study was to enhance students' proficiency in documenting interview outcomes through the application of outdoor study methods. The participants were 10 students selected from an elementary school in Kapanewon Samigaluh, Kulon Progo Regency, comprising 6 boys and 4 girls. The research utilized a classroom action research approach. The findings indicated a progressive improvement in students' ability to write down interview results in each cycle. During the initial cycle, students achieved an average score of 11.1 with a success rate of 50%, which falls within the category of